The circular insanity of philosophy: an aesthetic vision (Lebenswelt. Aesthetics and philosophy of experience., 2023)
A long tradition, whose echo is still perceptible in some contemporary reflections, combines philosophy and melancholy, often indentifying melancholy as the beginning of philosophy. But rereading the Freud’s Mourning and Melancholia, the «circular insanity» shows two sides, depressive and maniac. Once the double nature of the «circular insanity» has been taken into consideration, it can be reiterated that melancholy is connected to philosophy not only with regard of its beginning but also to its (temporary) end, approached through Wittgenstein's reflection on the miracle and the mystical as the extinction of the philosophical question. In this perspective, the whole cycle of philosophy, from its depressive beginning to its maniacal outcome, undergoes an aesthetic consideration, in which what is more important is the how of experience rather than its what. Finally, the aesthetic point of view on the connection between melancholy and philosophy makes it possible to reconsider the very status of that research that presents itself as 'love of knowledge'.